PRAKTEK SUPERVISI GURU PAI SEKOLAH DASAR BERBASIS ICT DI KEDUNGREJA CILACAP - Sarno Sarno (QALAM: JURNAL PENDIDIKAN ISLAM, 2020)
It is undeniable that technological advancements in the field of information and communication are currently developing very rapidly. Technological advances have spread throughout the world in various activities in our daily lives. In the world of education it is also like that, for example in supervision activities, supervision activities by PAI Supervisors on Islamic Religious Education teachers in Elementary Schools are also required at present to be more creative in conducting supervision because of the influence of the times such as the progress of IT. At this time the supervisor is demanded to be able and skilled in utilizing the progress of IT to conduct supervision, this is done to keep up with the rapidly advancing times and also as improving the progress of school technology.